The Relationship of Product Design Quality and User Satisfaction for Academic Potential Tests Simulation Mobile Application Development with User-Centered Design - Anggy Trisnadoli; Istianah Muslim; Indah Lestari; Adella Syafira (International ABEC, 2022)
In developing a user-centered software, there are various things that need to be considered, such as expectations for better development, as well as quite different stages of work. One method that can be used to develop software that is in accordance with the user’s expectation is User-Centered Design (UCD), this method is proven to have produced a software that is believed to have a good quality value. The Academic Potential Test Mobile Application is a mobile-based application that can be used as a simulation to assess and measure the value of a person's academic potential. This mobile application was developed specifically to be used as a supporter in the New Student Admission process at Politeknik Caltex Riau. This mobile application is developed using the user-centred design method, by using this method the application product is also expected to have a good value. User satisfaction is an absolute opinion given by application users shortly after they use the application, although it is of good value in terms of product quality, sometimes user satisfaction is neglected. It is necessary to keep measuring user satisfaction even though the product quality value has been declared good. Another study shows that there is a relationship between the value of product quality and the value of user satisfaction for desktop application. So, in this research we would like to prove the relationship between those two variables, in the development of mobile applications then it will become a reference for other developers in developing a mobile application with User-Centered Design method.